АТОҚЛИ ОТЛАРНИНГ ТИЛ ЛУҒАВИЙ ҚАТЛАМИДАГИ ЎРНИ - Бахтиёрова, М.Б. (SCIENCE and SOCIETY, 2021)
The article examines nouns from the point of view of linguacultural . There is presented an overview of the works of scientists who have contributed to the development of cognitive linguistics. The study of each idea as a concept is based on helping to clearly verbalize the origins of the nation and the culture of the people.